State power as a means of oppression towards women: A study of Margaret Atwood’s The Handmaid’s Tale - Begum, Tanjina (BRAC University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2021.